The Evolutionary Biology of Musical Rhythm: Was Darwin Wrong? - Nournamaee, Maryam; Patel, Aniruddh D. (LANGUAGE ART, 2022)
In The Descent of Man, Darwin speculated that our capacity for musical rhythm reflects basic aspects of brain function broadly shared among animals. Although this remains an appealing idea, it is being challenged by modern cross-species research. This research hints that our capacity to synchronize to a beat, i.e., to move in time with a perceived pulse in a manner that is predictive and flexible across a broad range of tempi, may be shared by only a few other species. Is this really the case? If so, it would have important implications for our understanding of the evolution of human musicality.